Evaluation of quality of partial caging by a planar two-fingered hand. (1st February 2016) - Makita, Satoshi; Nagata, Kazuyuki
Abstract : In partial caging, an object is partially constrained by robots and is able to escape from there. Although complete caging ensures the hand never releases the confined object, insufficient degrees of freedom of robots does not often satisfy the conditions for caging. Partial caging, however, can be accomplished even by robots having such mechanical restriction. We consider a case that an object moves in the semi-closed region formed by a planar robot hand with two fingers, as an example of partial caging in two-dimensional space. Then the parameters of fingers: joint angles interfere in the object motion to escape from the hand through the gap between the fingertips. Some simulation results show differences of difficulty of escaping according to arrangement of fingers, and factors interfering in the difficulty are analyzed. Additionally, we also evaluate ease of entering the hand through the gap and define an ability index of robot hand for partial caging with the above two evaluation scores. Then a high index score indicates that the hand assumed to be able to capture objects easily and confine it without any finger motion. It can be utilized for mechanical design and controlling strategies of robots in capturing objects. Graphical Abstract: